2000
DOI: 10.1164/ajrccm.162.3.9909074
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Bronchoalveolar Lavage Indices Associated with Radiographic Classification in Coal Miners

Abstract: Previous studies on symptomatic coal miners have shown that alveolar macrophages, recovered by bronchoalveolar lavage (BAL), release excessive amounts of reactive oxygen species (ROS) and inflammatory cytokines. It has been proposed that these secretions may mediate cell injury and initiate the disease process. We hypothesized that acellular bronchoalveolar lavage fluid (BALF) indices in coal miners chronically exposed to coal dust may reflect the status of important homeostatic modulations in the lung that le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
30
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(35 citation statements)
references
References 30 publications
4
30
1
Order By: Relevance
“…This is in agreement with previous studies showing specific up-regulation of this isoform in NLF from smokers (Ghafouri et al 2002) and patients with allergic rhinitis (Ghafouri et al 2006). Other studies has showed increased levels of alpha-1-antitrypsin in bronchoalveolar lavage fluid (BALF) in coal miners with pneumoconiosis (Vallyathan et al 2000), as well as in people nonoccupationally exposed to asbestos (Archimandriti et al 2009). Lactoferrin is a protein with diverse effects, but is mostly recognized as having antimicrobial properties.…”
Section: Discussionsupporting
confidence: 92%
“…This is in agreement with previous studies showing specific up-regulation of this isoform in NLF from smokers (Ghafouri et al 2002) and patients with allergic rhinitis (Ghafouri et al 2006). Other studies has showed increased levels of alpha-1-antitrypsin in bronchoalveolar lavage fluid (BALF) in coal miners with pneumoconiosis (Vallyathan et al 2000), as well as in people nonoccupationally exposed to asbestos (Archimandriti et al 2009). Lactoferrin is a protein with diverse effects, but is mostly recognized as having antimicrobial properties.…”
Section: Discussionsupporting
confidence: 92%
“…Taken together, the findings of this study were difficult for the authors to resolve given the strong evidence for pro-inflammatory lung effects of a variety of metal-rich particulates such as diesel exhaust, residual oil fly ash, particulate matter, zinc oxide, and coal dust (Blanc et al, 1991;Carter et al, 1997;Salvi et al, 2000;Vallyathan et al, 2000;Ulrich et al, 2002). The authors speculated that the high transitional metal levels in the lung must somehow impair lung host defense and provide a temporary window for infection.…”
Section: Human Immunotoxicity Studiesmentioning
confidence: 84%
“…The in vitro response to residual oil fly ash, a model for iron-rich PM, can be abolished by incubation with the iron chelator desferrioxamine [21], and it has been hypothesised that air pollution exerts its inflammatory effect via oxidative stress, catalysed by metals present in PM. Certain other occupational particulates, such as zinc oxide in metal fume fever [32] and dust from coal mines [33], have also been linked with release of cytokines and influx into the airways of inflammatory cells.…”
Section: Discussionmentioning
confidence: 99%